ダイ43ジ ナンキョク チイキ カンソクタイ ケンチク ブモン ホウコク (フクム ドームフジ カンソク キョテン ノ ヤネ レベル ソクリョウ ケッカ) - 依田, 恒之; ヨダ, ツネユキ; Yoda, Tsuneyuki (2004)
P(論文) 第43次観測隊の建設部門として,二人(依田恒之と富樫幸一)が越冬した.昭和基地では,2001年12月19日から夏期作業を開始し,63日間で1110人日の建設作業を行った.第2廃棄物保管庫兼車庫の建設は,297人日で作業日人員の1/4以上の人員が掛り夏期建設作業のメイン工事となった.昭和基地越冬中はメンテナンス作業を行い,2002年10月12日からドームふじ旅行隊に参加し,ドームふじ観測拠点でボーリング用トレンチ掘削場の建設を11月14日から2003年1月23日まで実施した.当初の設定雪面より多く雪が積もっておりトレンチ掘削では,予定量より大幅に作業人日が増え,掘削には大変苦労した. Tsuneyuki Yoda and Kouichi Togashi participated in the 43rd Japanese Antarctic Expedition as architechts of the wintering party. The construction work started from December 19, 2001, and lasted 63days with total working hours of 1100 person* days. The main project was the construction of the 2nd warehouse, which required 297 person* days (one-fourth of the total working hours). They left for Dome Fuji Station as members of the traverse party on October 12, and worked on the construction of a new snow trench at the ice core drilling site during November 14, 2002-January 23, 2003. Accumulated snow cover was thicker than expected, and trenching required 103 working hours. departmental bulletin paper